FRI0350 FACTORS ASSOCIATED WITH PERIPHERAL EROSIVE RADIOGRAPHIC DISEASE IN A CONSECUTIVE SERIES OF 794 PSA PATIENTS. (2nd June 2020) - Catanoso, M. G.; Macchioni, P.; Marchesoni, A.; D'angelo, S.; Ramonda, R.; Cauli, A.; Perrotta, F.; Bortolotti, R.; Lofrano, M.; Rotunno, L.; Lorenzin, M. G.; Valesini, G.; et al.
Abstract : Background: Few studies have examined the correlation between clinical demographic and laboratory parameters with peripherical radiological erosive disease in PsA pts. Objectives: To examine the association between clinical, demographical and laboratory data and the presence of radiographic erosions (RE) in the peripheral joints of psoriatic arthritis (PsA) pts. Methods: A cross-sectional study was conducted in consecutive patients with PsA afferring 7 rheumatological italian tertiary care centers. Demographical, clinical, laboratory and imaging data were collected according to a standardized protocol. A patient was considered as affected by erosive disease (ED) if at least one joint presented radiographic erosions at hand and/or feet rx examination. Patients with ED at early rx examination (before 5 y from disease diagnosis) were considered as early ED (EED) pts and pts without ED at 6 y or more rx examination from disease diagnosis were considered as not EED (NEED).The association between the presence of joint erosions and demographical, clinical and laboratory data was assessed using logistic regression analysis. The results were expressed in terms odds ratios (OR), and 95% confidence intervals (CI). Results: Rx hand and feet examination were available for analysis in 492/794 (39.9 % females, mean age 53.3 ± 13.2 y, mean PsA duration 16.9 ± 16.8 y, ED 171 pts). 48 pts had EED and 133 pts had NEED. At univariate analyses factors significantly associated with EED (p < 0.20) were PsA duration (OR=0.979, 95%CI 0.953-1.006, p = 0.119), diagnostic delay (OR=1.077, 95%CI 1.018-1.138, p = 0.009), history of peripheral enthesitis (OR=2.308, 95%CI 0.904-5.888, p= 0.080), hypertrigliceridemia (OR=2.756, 95%CI 0.997-7.618, p = 0.0.051), hypercholesterolemia (OR=1.687, 95%CI 0.777-3.661, p = 0.186), hyperuricemia (OR=0.450, 95%CI 0.174-1.166, p = 0.10), use of biological agents (OR=1.712, 95%CI 0.873-3.355, p=0.118). Factors significantly associated with EED at multivariate regression analyses were diagnostic delay (OR = 1.11, 95% CI: 1.01, 1.22), history of enthesitis (OR = 3.15, 95% CI: 1.23, 8.22), use of therapy with biological agents (OR = 3.60, 95% CI: 1.31, 9.85) with protective effect of hyperuricemia (OR = 0.25, 95% CI: 0.07, 0.90). Conclusion: The presence of EED in a group of consecutive PsA patients is correlated to diagnostic delay and history of enthesitis. Longitudinal study may confirm these associations. Disclosure of Interests: Maria Grazia Catanoso: None declared, Pierluigi Macchioni: None declared, Antonio Marchesoni Speakers bureau: Abbvie, Pfizer, UCB, Novartis, Celgene, Eli Lilly, Salvatore D'Angelo Speakers bureau: AbbVie, Biogen, BMS, Celgene, Janssen, Lilly, MSD, Novartis, Pfizer, Sanofi, and UCB, Roberta Ramonda Speakers bureau: Novartis, Celgene, Janssen, Pfizer, Abbvie, Lilly, Alberto Cauli: None declared, fabio perrotta: None declared, Roberto Bortolotti: None declared, mariana lofrano: None declared, laura rotunno: None declared, maria grazia lorenzin: None declared, Guido Valesini: None declared, giovanni mathieu: None declared, Giuseppe Paolazzi: None declared, Carlo Salvarani Grant/research support from: consulting and investigator fees from Abbvie, Pfizer, MSD, Roche, Celgene, Novartis, Consultant of: consulting and investigator fees from Abbvie, Pfizer, MSD, Roche, Celgene, Novartis